Pemberdayaan Masyarakat untuk Pengolahan Produk Gelato dengan Penambahan Dadih sebagai Pangan Sumber Probiotik - Tinda Afriani; Indri Juliyarsi; Sri Melia; Jaswandi Jaswandi; Elly Roza; Melati Trisnaneng Putri; Mylaufa Asyraf (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
One of West Sumatra's popular dairy products is Dadih, a traditional food made from buffalo milk and processed by natural fermentation in a bamboo tube. Dadih could be a local food enriched by a natural probiotic source. However, the Dadih is rarely processed into other food products due to a need for more information for farmers and the community. The innovation can be done by using it as an additional ingredient in a product, such as Gelato. Making Gelato has simple steps mixing all the ingredients with the addition of curd. This community engagement activity started with education on the good of Dadih's nutrition, followed by direct assistance in making Gelato, and then counselling groups of farmers in the district of 50 Kota. The activities were conducted on July 24, 2022, and were well responded to by the groups of farmers. Gelato processing that was carried out could produce with Dadih.